Comparison of different cleanup procedures for oil crops based on the development of a trace analytical method for the determination of pyraclostrobin and epoxiconazole. Issue 24 (6th November 2014) - Pan, Xinglu; Dong, Fengshou; Xu, Jun; Liu, Xingang; Cheng, Youpu; Chen, Zenglong; Liu, Na; Chen, Xixi; Tao, Yan; Zheng, Yongquan
<x xml:space="preserve">Abstract</x> The effects of different cleanup procedures in removing high‐molecular‐mass lipids and natural colorants from oil‐crop extracts, including dispersive solid‐phase extraction, low‐temperature precipitation and gel permeation chromatography, were studied. The pigment removal, lipid quantity, and matrix effects of the three cleanup methods were evaluated. Results indicated that the gel permeation chromatography method is the most effective way to compare the dispersive solid‐phase extraction and low‐temperature precipitation. Pyraclostrobin and epoxiconazole applied extensively in oil‐crop production were selected as typical pesticides to study and a trace analytical method was developed by gel permeation chromatography and ultra high performance liquid chromatography with tandem mass spectrometry. Average recoveries of the target pesticides at three levels (10, 50, and 100 μg/kg) were in the range of 74.7–96.8% with relative standard deviation values below 9.2%. The limits of detection did not exceed 0.46 μg/kg, whereas the limits of quantification were below 1.54 μg/kg and much lower than maximum residue limit in all matrices. This study may provide the essential data for optimizing the analytical method of pesticides in oil‐crop samples.